Toxicity of Heavy Metals on Germination and Seedling Growth of Salicornia brachiata - Ashwani Kumar Srivastava1, Anubha Sharma1* Iti Gontia-Mishra2 (Journal of Phytology, 2011)
Seed is a developmental stage that is highly protective against external stresses in the plant life cycle. In this study, we analyzed toxicity of heavy metals (Cd2+, Ni2+and As3+) on seed germination and seedling growth in a halophyte Salicornia brachiata. Germination percentage for Ni2+ is lower than Cd2+and As3+ metal at 200 µM concentration. Shoot length and root length decreased significantly upto 400 µM and 100 µM of Ni2+ and As3+ respectively While in case of Cd2+ seedlings could survive up to 300 µM concentration with a minor reduction in growth. Salicornia brachiata can serve as substantially important plant species for phytoremediation of heavy metals at lower concentrations in saline areas.